Synthesis of proteases by a species of anamorphic filamentous fungus for application in industrial processes (Research, Society and Development, 2022)
The use of enzymes in food processing, detergent and textile industries is constantly on the rise. The application of proteolytic enzymes of microbial origin stands out in the industrial sector due to the desirable conditions for use in biotechnological processes, they are natural and non-toxic biocatalysts. The objective of this research was to evaluate the production and characterize proteases synthesized by Aspergillus flavus. The matrix culture was prepared in Sabouraud agar and kept for seven days at 25 ºC. Then, the species was cultivated in liquid medium [GYP (glucose, yeast extract and peptone)].  The fermentation was conducted on an orbital shaker 150 rpm, 25 ºC. After eight days the mycelial mass was separated by vacuum filtration on Whatman No. 1 paper and the crude extract recovered, and filtered on 0.45μL polyethersulfonic membrane. For determination of protease activity, 1% (w/v) azocasein in Tris-HCl buffer pH 7.2 was used as substrate.  The results showed that A. flavus excreted proteases in all the media tested, but with significant activity in GYP medium (90.13 U/mL). The proteases showed optimum activity at pH 5 and temperature 50°C.  These results suggest that these enzymes can be used in several industrial segments, such as food, textile and bakery.